Pengaruh Insight Media Sosial Instagram Terhadap Penjualan Produk Online - Handry Eldo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was created with the aim of finding out the influence of Instagram social media insights on online product sales on the Instagram social media platform.